Semantics of legal concepts and natural kind terms: D. Patterson’s arguments - A. B. Didikin (Омский научный вестник: Серия "Общество. История. Современность")
The paper is devoted to the analysis of the arguments of the american legal philosopher Dennis Patterson regarding the applicability of the natural kinds terms to the semantics of the legal language. Based on the Ronald Dworkin’s theory of law, reasonable criticized by D. Patterson, the features of the formation and interpretation of legal concepts are considered. Arguments are presented that demonstrate the content of R. Dworkin and D. Patterson’s methodological approach to the interpretation of the semantics of legal concepts as well as argumentation regarding the normativity of legal reality, the objects of which are displayed in the content of legal concepts